Emerging Adulthood in Taylor Swift's Folklore: A Lyrical and Semiotic Interpretation - Getta Eniddia Finery; Titis Setyabudi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The aim of this research is to examines how Taylor Swift's Folklore represents the psychological and emotional dimensions of emerging adulthood. Focusing on six selected songs "The 1," "Exile," "Cardigan," "Mirrorball," "This Is Me Trying," and "August". The study analyses how metaphors, narrative imagery, and lyrical symbols construct meanings related to identity exploration, instability, emotional vulnerability, nostalgia, feeling in-between, and sense of possibilities. The research employs qualitative descriptive using Roland Barthes' semiotic approach, examining denotative and connotative meanings within six selected songs from Folklore. The interpretation is guided by Arnett's (2000) Emerging Adulthood Theory. The analysis is also supported by Miles and Huberman's interactive data analysis model, including data reduction, data display, and conclusion drawing. The findings demonstrated that Folklore constructs emerging adulthood as a period of emotional turbulence, fragile self-concept, nostalgia, coping behaviour, and identity negotiation. Symbols such as Mirrorball, cardigan, and seasonal imagery reflect vulnerability, memory, and transition. These findings demonstrate that contemporary song lyrics function not only as artistic expression but also as cultural texts that reflect psychological development during emerging adulthood. This study contributes to literary and cultural studies by showing how popular music articulates emotional meanings connected to life transitions and identify formations.